TEARING AND DISCHRONAL SUBDUCTION OF THE INDIAN CONTINENTAL SLAB: EVIDENCE FROM CENOZOIC GANGDESE VOLCANO-MAGMATIC ROCKS IN SOUTH TIBET - Hou Z.Q.; Yang Z.M.; Zhao Z.D.; Gao Y.F.; Jiang W. (My University, 2006)
The Gangdese tectono-magmatic belt in the Tibetan continental collision zone can be divided, at least, three segments, i. e., western Gangdese (west to 85°E), middle Gangdese (85°E to 90°E) and eastern Gangdese (east to 90°E), on the basis of the aeromagnetic anomalies in the Tibetan plateau. The middle Gangdese is bounded by Xurucuo-Dangruoyongcuo rift (west) and Naqu-Gulu rift (east), along which the Miocene ultra-potassic lavas and Nianqingtanggula granitoid plutons with associated potassic lavas were developed, respectively. A 300km wide, NNE-extending negative aeromagnetic anomaly zone occurs in the middle Gangdese. In the segment, the Xigaze fore-arc basin and ≈ 5000m thick Paleocene Linzizong volcanic successions were preserved, and mid-Miocene porphyry-type Cu-Mo mineralization was developed. In contrast, the western Gangdese (west to 85°E) is characterized by development of positive aeromagnetic anomaly, thrust-napped structures, collisonal granite intrusions and Miocene potassic and ultra-potassic lavas, as well as orogenic-type Au mineralization. The eastern Gangdese (east to 90°E) is characterized by large-scale strike-slip faulting system and collisional granitoids, and absence of the Miocene ultra-potassic lavas. The Linzizong volcanic rocks widely developed along the whole Gangdese and show identical geochemical characteristics, indicating that initiation collision between Indian and Asian continents (65Ma) and subsequent suduction of the Indian continental slab (65 ~ 50Ma) are generally isochronal along the whole Gangdese. However, spatial distribution of the Miocene ultra-potassic lavas and huge granitoid balitholiths imply that dischronal subduction probably occurred prior to the mid-Miocene. The Sr-Nd isotopic signatures Miocene ultra-potassic lavas in the western Gangdese suggest that the Indian continental crustal materials were involved in generating these magmas. However, this involving of the Indian continental crust has been not observed in the middle and eastern Gangdese. A plausible interpretation is that tearing of the Indian continental slab probably resulted in dischronal subduction along the Indo-Asian collision zone. The subducted continental slab west to 85°E has a gently angle, and probably reached in the Bangong-Nujiang suture, whereas the continental slab east to 90°E deeply subducted, tnus most likely didn't get across the Indus-Yarlung suture, during Miocene period. Upwelling of asthenospheric material through the slab tear window triggered partial melting of the subcontinental lithosphere and led to magmas migrating upwards along the rifting zone coupled with underlying tear zones. The continental slab between 85°E and 90°E probably took place intensively broken, which resulted in upwelling of hot, asthenospheric materials, in turn caused negative aeromagnetic anomalies in the Tibetan plateau.
Keywords: CENOZOIC IGNEOUS ROCKS; DISCHRONAL SUBDUCTION; INDIAN CONTINENT; SLAB TEARING; TIBETAN PLATEAU; Кайнозой::Неоген::Миоцен; Кайнозой::Палеоген::Эоцен; Кайнозой::Палеоген::Палеоцен; Cenozoic::Neogene::Miocene; Cenozoic::Paleogene::Eocene; Cenozoic::Paleogene::Paleocene